Shattered Glass in Birmingham : My Family's Fight for Civil Rights, 1961-1964 - Jimerson, Randall C. (Book collections on Project MUSE., 2014)
Shattered Glass in Birmingham traces the experiences of a white northern family during the climax of the civil rights movement in Alabama's largest city. Recounted primarily from Randall Jimerson's perspective as one of five children of Reverend Norman C. ""Jim"" Jimerson, executive director of the Alabama Council on Human Relations, the narrative explores the public and private impact of the civil rights struggle. Based on extensive archival research as well as oral histories, Shattered Glass in Birmingham offers the reader a ground-level view of prejudice, discrimination, violence, and co.